(3GdZjK GdgGeY aj TQM LeY GdLhGeYs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s; (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ,J (B771 (3g` s ((3Ydi GdObQhSs)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CeG HYO MeO Gddg agPG JYdjb hLjR Ydi LeY GdLhGeY dTjNfG bGVi GdbVGI JGL GdOjf GdSHci GbJUQ ajg Ydi Md GddaX s
(3BNQgG (B:s
(3hEfeG gh YLR hegGfI hGdSYjO ef hab ddUOb bGd eDdag gPG BNQ eG JjSQ LeYg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3LGA ai GdfSNI Cf GdeDda aQZ ef JCdjag SfI (B824s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs